2017
DOI: 10.12816/0037829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiabetic and Antioxidant Activity of Aegle Marmelos L. Correa Fruit Extract in the Diabetic Rats

Abstract: Background: Diabetes mellitus is regarded as a serious chronic disease that carries a high risk for considerable complications. The use of natural plant products for management of diabetes is increasing due to their minimal side-effects and economical aspects. Aegle marmelos L. Correa (A. marmelos), family Rutaceae is highly reputed medicinal plant commonly known as bael. A. marmelos fruit is widely used in folk medicine for the treatment of diabetes mellitus. Aim of the work: This study was aimed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…However, after Aegle marmelos ethanolic fruit extract administration, serum blood glucose levels was significantly reduced. The reduction in blood glucose was likely due to the presence of coumarins and flavonoids present in the Aegle marmelos fruit extract that may have caused regeneration of the damaged pancreatic beta cells and improved the insulin secretion from the remnant pancreatic beta cells 71 , 72 . The decreased blood glucose level diminishes the fuel source of the rapid proliferating neoplastic cells and thus reduces the tumor growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, after Aegle marmelos ethanolic fruit extract administration, serum blood glucose levels was significantly reduced. The reduction in blood glucose was likely due to the presence of coumarins and flavonoids present in the Aegle marmelos fruit extract that may have caused regeneration of the damaged pancreatic beta cells and improved the insulin secretion from the remnant pancreatic beta cells 71 , 72 . The decreased blood glucose level diminishes the fuel source of the rapid proliferating neoplastic cells and thus reduces the tumor growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the antioxidant activity was also studied on rats by in vivo method, where rats have been delighted with extracts of T. polium, which showed a considerable antioxidant activity as that of α-tocopherol (positive control) in the DPPH test. At the doses of 50 mg/kg and 100 mg/kg, the extracts of T. polium extensively amplified the total antioxidant power and reduced the thiobarbituric acid reactive substances in [93] rats, compared to the control [66]. In vitro studies of aqueous extract of T. polium can also efficiently reduce oxidative progressions with significant antioxidant activity [67].…”
Section: Teucrium Poliummentioning
confidence: 97%
“…A fruit lectin extract with an IC 50 of 3.36 μg/ml had greater efficiency than the usual medication metformin at increasing glucose uptake by yeast cells. This study found that A. marmelos fruit extract had hypoglycemic activity, which could be attributed to its antioxidant activity and high content of active constituents [ 53 ]. As a result, the various parts of A. marmelos plant could be beneficial as a portion of healthy food and in developing antidiabetic drugs.…”
Section: Pharmacological Activitymentioning
confidence: 99%